Pear rust in Belarus because of fungus Gymnosporangium sabinae (Dicks.) G. Winter invasion - Poliksenova, Valentina D. (Experimental Biology and Biotechnology, 2022)
Pear rust in Belarus was first registered in 2007, and after 12 years the disease acquired the character of epiphytosis. A map of the distribution of pear rust in the republic has been compiled. The symptoms of damage to pear and juniper, spores of the causative agent (fungus Gymnosporangium sabinae (Dicks.) G. Winter) are described and illustrated. It has been shown that aecio- and teliospores overwintered in the shoots do not germinate in the next growing season. The teliospores of the current year on juniper germinate not only with phragmobasidia with basidiospores, but also with mycelium, which probably ensures the re-infection of this host plant. The high infectious potential of both pear (up to 15 mln aeciospores per 1 cm2 ) and juniper (2 mln teliospores per 1 cm2 ) was determined. The death due to rust of annual shoots of pear and individual plants of the Cossack juniper was ascertained. The invasion of G. sabinae on the territory of Belarus coincides with the wide introduction of susceptible species of juniper into landscaping.
Keywords: pear rust; Gymnosporangium sabinae (Dicks.) G. Winter; juniper; invasion; Belarus